Willingness to pay for recreational benefits in Sagada, Philippines a contingent valuation study - Abansi, Corazon L. (Cordillera Review : Journal of Philippine Culture and Society, 2012)
Using contingent valuation method, this study attempts to estimate the value of recreational benefits that accrue to both local and foreign tourists in Sagada, Mt. Province, Philippines. A dichotomous choice format is used to elicit information about tourists' willingness to pay (WTP) for programs that will protect and preserve Sagada's recreational environment. Tourists rank cave activities, waterfall activities, and trekking/nature hike as the three most enjoyable experiences in this popular tourist destination. Tourists' awareness and ranking of critical environmental issues such as vandalism in caves and desecration of burial sites are indicative of their appreciation for a well-preserved natural and cultural heritage. The WTP estimates derived by logistic regression are higher for foreign tourists than for locals, though both figures are higher than the entrance fee that tourists are currently being charged in Sagada. These estimates reflect both sue and non-use values held by tourists, including the opportunity to enjoy Sagada again in the future, and bequest value, or the site's protection and preservation for future generations. Bid amount and income are significant variables affecting WTP for both groups, serving as the basis for a fee increase under a two-tiered pricing system. Disaggregated pricing schemes per tourist spot and the attendant policy guidelines in the administration of the environmental potential fund are proposed for future investigation.